How Much Do Teachers Earn? - Claudia Piras; William D. Savedoff (Inter-American Development Bank, Office of the Chief Economist, 1998)
In the continuing debate over how to improve education systems, many people argue that teachers` salaries need to be increased. This paper seeks to establish a reliable method for analyzing the issue using household survey data from Bolivia.
Keywords: 330; Einkommen; Lohnstruktur; Lehrkräfte; Bolivien